Observations sur la biologie et la dyhamique du maouereau espagnol (scomber japonicus colias gmelin) dans l’Atlantioue est central - Staicu, Ionel; Maxim, Constantin (Cercetări Marine - Recherches Marines, 2026)
This paper presents the results of the investigations in the period 1972-1973 on chub mackerel’s growth from north African Coast of Atlantic Ocean. At the same time lengths and ages frequences of catches, and sex ratio are presented, too. It points out a different lengths structure confronted by 1958- 1963 period.